U.S. Senate Debate 2002 (2002)
This was the U.S. Senate Debate in Launer Auditorium on October 24, 2002. U.S. Senator Jean Carnahan (D-MO), Jim Talent (R), Tamara Millay (L) and Green Party candidate Daniel Romano (R) spoke..